Disciplining trade-distorting support to cotton in the US: an unresolved issue at the WTO negotiations - Sachin Kumar Sharma; Aditi Sawant; Parkhi Vats; Sadhna Naik; Teesta Lahiri (Agricultural Economics Research Review, 2023)
Despite the higher cost of production, the developed country members of the World Trade Organization (WTO) like the United States (US) enjoy an artificial comparative advantage in the international cotton markets due to huge subsidies and entitlements at the expense of the poor farmers in developing countries. This paper critically examines the effects of various proposals in the WTO negotiations on the flexibilities to the US to support its cotton farmers. The paper finds that agreeing on any proposal, and implementing it, would considerably reduce the US policy space and benefit millions of developing country cotton farmers.